"El camino por recorrer": Parent Perspectives on Early Autism Intervention in Mexico. (February 2023) - Hampton, Lauren H.; Herrera-Carrillo, Francisco Eugenio; Vargas Londono, Fabiola; Villarreal, Enrique G.; Martínez Cueto, Ana Paula
Parents of children on the autism spectrum are important members of their child's early intervention team, yet there are multiple barriers to translating evidence-based parent-mediated interventions in Mexico. We examined early intervention needs in the Mexican population and compared these needs to those of the Latinx Spanish-speaking population in the United States. A total of 242 parents in Mexico and the United States responded to our survey. Results indicate that few parents in Mexico receive parent training during early intervention, parents in Mexico are less likely than Latinx parents in the United States to report speech-language services, and most parents across both groups reported that they wished that they had more tools to support development and address challenging behavior. Responses to open-ended survey questions were coded qualitatively for themes and subthemes. We provide four recommendations for adapting early interventions in Mexico and discuss implications for future research and practice.